FAKTOR YANG BERHUBUNGAN DENGAN LAMA HARI RAWAT INAP PASIEN DEMAM BERDARAH DENGUE (DBD) DI RUMAH SAKIT UMUM DAERAH KOTA KENDARI TAHUN 2017 - Syahwal, Muhammad (Preventif Journal, 2018)
Dengue Hemorrhagic Fever (DHF) disease is still the second largest contributor as the most hospitalized disease inhospital. Beginning date obtained from the General Hospital Kendari city in 2017 recorded the March period 24patients (9,48%) of 253 cases of DHF hospitalization. The purpose of this research is to know related factors tothe length of the day of DHF patient hospitalization at Kendari City Hospital . Type of this research is analyticsurvey research with cross sectional study design . The population in this study were all denguefever patients being treated at Kendari City Hospital centre which in January - March 2017 that 66 people whilethe sample of research as many as 24 respondents. Analitic research results using statistical test of chisquare(X 2) and the alternative test fishers exact test (p) m show there is relationship are ; age, history ofbleeding, result of laboratory examination (thrombocyte) and duration of illness before being treated with longdays of DHF patient care in Kendari City Hospital. Suggested to nurses who served in Kendari City Hospitalto always improve the quality of nursing services provided to patients with DHF by always increasing socializationprevention and handling of dengue cases in patients and their families .